2017
DOI: 10.7150/jca.16870
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Inflammatory Breast Cancer Compared to Non-Inflammatory Breast Cancer in the Setting of High-Dose Chemotherapy with Autologous Hematopoietic Cell Transplantation

Abstract: Introduction: Inflammatory breast cancer (IBC) is a rare aggressive form of breast cancer. It is well known that the long-term survival and progression-free survival of IBC are worse than that of non-IBC. We report the long term outcomes of patients with IBC and non-IBC who had undergone high-dose chemotherapy (HDC) with autologous hematopoietic cell transplantation (AHCT).Methods: All 3387 patients with IBC or non-IBC who underwent HDC with AHCT between1990-2002 and registered with CIBMTR were included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In 1997, the International Blood and Marrow Transplant Registry reported a 3-year OS rate of 52% in 253 IBC patients treated with HDCT with AHSCT [40] . A larger and updated registry of HDCT with AHSCT, comprising 527 IBC patients and 2,860 non-IBC patients from the Center for International Blood and Marrow Transplant Research, reported a 10-year OS rate of approximately 30% with no difference between IBC and non-IBC [41] . However, among non-metastatic patients with no evidence of disease at transplant, the 10-year OS was worse for IBC patients than for non-IBC patients (37% vs. 45%, respectively; p = 0.03).…”
Section: Developments Of Systemic Treatment For Ibcmentioning
confidence: 99%
“…In 1997, the International Blood and Marrow Transplant Registry reported a 3-year OS rate of 52% in 253 IBC patients treated with HDCT with AHSCT [40] . A larger and updated registry of HDCT with AHSCT, comprising 527 IBC patients and 2,860 non-IBC patients from the Center for International Blood and Marrow Transplant Research, reported a 10-year OS rate of approximately 30% with no difference between IBC and non-IBC [41] . However, among non-metastatic patients with no evidence of disease at transplant, the 10-year OS was worse for IBC patients than for non-IBC patients (37% vs. 45%, respectively; p = 0.03).…”
Section: Developments Of Systemic Treatment For Ibcmentioning
confidence: 99%
“…So far, research on treatment of IBC has focused primarily on improving systemic therapy. Nonetheless, clinicians have realized the complexity associated with IBC and have mentioned that the prognosis of these patients remain poor [ 27 ]. Therefore, there is a need to develop an innovative strategy for drug delivery to treat IBC.…”
Section: Introductionmentioning
confidence: 99%
“…It substantially improves the survival rate of patients with IBC and non-IBC. A recent study reported, 71 and 31%, 5 and 10 year OS rates, respectively, in IBC patients [ 5 ] [ 6 ].…”
Section: Introductionmentioning
confidence: 99%